On some properties of grounding nonuniform sets of modal conjunctions - Katarzyniak, Radosław Piotr (Zielona Góra: Uniwersytet Zielonogórski)
A language grounding problem is considered for nonuniform sets of modal conjunctions consisting of conjunctions extended with more than one modal operator of knowledge, belief or possibility. The grounding is considered in the context of semiotic triangles built from language symbols, communicative cognitive agents and external objects.
Keywords: cognitive agent; semantic communication; language grounding; conjunction; modality; artificial cognition